Forehand Smash Test Model for Junior Badminton Athletes - Wiyanto, Agus; Williyanto, Septian; Masri, Masri; Isdarianti, Novi Lidya; Wicahyani, Sri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
To determine how much the exercise program success rate, a valid and reliable test tool is needed. In this study, the researcher aims to develop a smash skill test model in badminton. The method in this study is a development research method with a sample size of 121 athletes. The steps taken in this research include (1) preliminary study (literature study and field study), (2) planning (conducting analysis), (3) initial draft design, (4) validation of the draft, (5) testing of group products minor and revisions, (6) large group trials and revisions, (7) final results. This study involved academicians and badminton practitioners with an â€œexcellentâ€ rating, which reached an average score of 3.66. This result research is a product of the development of a smash skill test model in badminton. This study concludes that the smash skill testâ€™s resulting form is valid and reliable, with a validity score of 0.688 and reliability of 0.870.